Co-engaging CD47 and CD19 with a bispecific antibody abrogates B-cell receptor/CD19 association leading to impaired B-cell proliferation. Issue 2 (17th February 2019) - Hatterer, Eric; Barba, Leticia; Noraz, Nelly; Daubeuf, Bruno; Aubry-Lachainaye, Jean-Pierre; von der Weid, Benoit; Richard, Françoise; Kosco-Vilbois, Marie; Ferlin, Walter; Shang, Limin; Buatois, Vanessa
ABSTRACT: CD19 is a B cell-specific receptor that regulates the threshold of B cell receptor (BCR)-mediated cell proliferation. A CD47xCD19 bispecific antibody (biAb) was generated to target and deplete B cells via multiple antibody-mediated mechanisms. Interestingly, the biAb, constructed of a CD19 binding arm and a CD47 binding arm, inhibited BCR-mediated B-cell proliferation with an effect even more potent than a CD19 monoclonal antibody (mAb). The inhibitory effect of the biAb was not attributable to CD47 binding because a monovalent or bivalent anti-CD47 mAb had no effect on B cell proliferation. Fluorescence resonance energy transfer analysis demonstrated that co-engaging CD19 and CD47 prevented CD19 clustering and its migration to BCR clusters, while only engaging CD19 (with a mAb) showed no impact on either CD19 clustering or migration. The lack of association between CD19 and the BCR resulted in decreased phosphorylation of CD19 upon BCR activation. Furthermore, the biAb differentially modulated BCR-induced gene expression compared to a CD19 mAb. Taken together, this unexpected role of CD47xCD19 co-ligation in inhibiting B cell proliferation illuminates a novel approach in which two B cell surface molecules can be tethered, to one another in order, which may provide a therapeutic benefit in settings of autoimmunity and B cell malignancies.